Perancangan Sistem Informasi Manajemen Karyawan Berbasis Web Menggunakan Model Extreme Programming pada PT Volar Mekanikal Teknologi X Luminous Creation - Suthansa Gading Prasetyo; Arya Ramandanu Roy Carol Rais; Khairil Yusuf; Wasis Haryono (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2025)
The advancement of information technology has encouraged companies to enhance operational efficiency through computerized systems, particularly in human resource management. PT Volar Mekanikal Teknologi x Luminous Creation faces challenges in manual attendance recording, unsystematic leave management, and a payroll system that lacks integration. Therefore, this study aims to design and implement a web-based Employee Management Information System using the Extreme Programming (XP) methodology. The system focuses on three main features: attendance tracking using GPS and selfie verification, online leave applications, and automated payroll calculation integrated with attendance data. The system development process includes planning, design using Unified Modeling Language (UML), coding with the Laravel framework and MySQL database, and testing through the Black-Box method. The implementation results show that the system effectively improves efficiency and accuracy in employee management, while also supporting the company’s operational activities in a more professional and structured manner.